Social innovation that connects people to coasts in the Anthropocene. (27th March 2023) - Celliers, Louis; Mañez Costa, María; Rölfer, Lena; Aswani, Shankar; Ferse, Sebastian
Abstract: Post-industrial society is driving global environmental change, which is a challenge for all generations, current and future. The Anthropocene is the geological epoch in which humans dominate and it is rooted in the past, present, and future. Future sustainability is building on the momentum of the fundamental importance of studying human dynamics and governance of coupled social and ecological systems. In the Anthropocene, social innovation may play a critical role in achieving new pathways to sustainability. This conventional narrative review uses a qualitative analysis anchored in the Grounded Theory Method and a systematic collection and analysis of papers to identify broad types of social innovations. Scientific journal articles published since 2018 were prioritised for inclusion. The six types of social innovation proposed are (a) authentic engagement; (b) artful and engaging communication; (c) urging and compelling change; (d) governance for social-ecological systems; (e) anticipation in governance; and (f) lived experiences and values. The six innovations proposed in this paper can be embedded within, and form part of, social action using a science–society compact for the sustainable development of coasts in the Anthropocene.